Fatigue life assessment of thin-walled welded joints under non-proportional load-time histories by the shear stress rate integral approach (Fracture and Structural Integrity, 2016)
Fatigue life tests under constant and variable amplitude loadings were performed on the tube-tube thin-walled welded specimens made of magnesium (AZ31 and AZ61) alloys. The tests included pure axial, pure torsional and combined in-phase and out-of-phase loadings with the load ratio "R ",?"R "? ? ?1. For the tests with variable amplitude loads a Gaußdistributed loading spectrum with LS ? 5?104 cycles was used. Since magnesium welds show a fatigue life reduction under out-of-phase loads, a stress-based method, which takes this behavior into account, is proposed. The out-of-phase loading results in rotating shear stress vectors in the section planes, which are not orthogonal to the surface. This fact is used in order to provide an out-of-phase measure of the load. This measure is computed as an area covered by the shear stress vectors in all planes over a certain time interval, its computation involves the shear stress and the shear stress rate vectors in the individual planes. Fatigue life evaluation for the variable amplitudes loadings is performed using the Palmgren-Miner linear damage accumulation, whereas the total damage of every cycle is split up into two components: the amplitude component and the out-of-phase component. In order to compute the two components a modification of the rainflow counting method, which keeps track of the time intervals, where the cycles occur, must be used. The proposed method also takes into account different slopes of the pure axial and the pure torsional Wöhler-line by means of a Wöhler-line interpolation for combined loadings.
Keywords: Magnesium welds; Multiaxial fatigue; Variable amplitude loading; Out-of-phase loading; Rainflow; Fatigue life assessment